MENANAMKAN KARAKTER OPTIMIS DENGAN PERMAINAN TRADISIONAL PADA ANAK USIA 7-9 TAHUN - Brigita Pundi Novena; Gregorius Ari Nugrahanta (Pedagogi, 2022)
The lack of character education, especially optimism, caused problems, one of which was cheating.  Optimistic character sounded foreign to early childhood, especially the lack of implementation of optimistic character education was lacking.  Therefore, this studied aims to develop a traditional game manual to cultivate optimistic characters in children aged 7-9 years.  The addie typed researched and development (rd) model was used as a method in this studied.  Ten certified teachers from various regions was involved in this researched for needed analysis, ten validators for expert judgment, and eight children was involved in a limited trial.  The results of this studied indicate that (1) the analysis of optimistic character needed shows an average of 2. 06 classified as "not good".  (2) the traditional game manual was developed through the addie (analyze, design, develop, implement and evaluate) steps.  (3) the manual had a score of 3. 79 (range 1-4) with the qualifications of “very good”, as well as suggestions of “no needed for revision”; (4) the implementation of the manual could affect the optimistic character.  The results of the significance test explained that t(7. ) = 32. 897, p = 0. 000 (p 0. 05).  The impact of the product was classified as having a "very large" effect with r = 0. 9968.  This shows that the implementation of traditional game manuals could affect 99. 36% of optimistic character changes in children aged 7-9 years.  85. 29% classified as "high" was a test of the effectiveness of the calculation of the n-gain score.